Metal complexation by histidine-rich peptides confers protective roles against cadmium stress in Escherichia coli as revealed by proteomics analysis - Isarankura-Na-Ayudhya,Patcharee; Thippakorn,Chadinee; Pannengpetch,Supitcha; Roytrakul,Sittiruk; Isarankura-Na-Ayudhya,Chartchalerm; Bunmee,Nipawan; Sawangnual,Suchitra; Prachayasittikul,Virapong (PeerJ, 2018)
The underlying mechanism and cellular responses of bacteria against toxic cadmium ions is still not fully understood. Herein, Escherichia coli TG1 expressing hexahistidine-green fluorescent protein (His6GFP) and cells expressing polyhistidine-fused to the outer membrane protein A (His-OmpA) were applied as models to investigate roles of cytoplasmic metal complexation and metal chelation at the surface membrane, respectively, upon exposure to cadmium stress. Two-dimensional gel electrophoresis (2-DE) and two-dimensional difference in gel electrophoresis (2D-DIGE) in conjunction with mass spectrometry-based protein identification had successfully revealed the low level expression of antioxidative enzymes and stress-responsive proteins such as manganese-superoxide dismutase (MnSOD; +1.65 fold), alkyl hydroperoxide reductase subunit C (AhpC; +1.03 fold) and DNA starvation/stationary phase protection protein (Dps; −1.02 fold) in cells expressing His6GFP in the presence of 0.2 mM cadmium ions. By contrarily, cadmium exposure led to the up-regulation of MnSOD of up to +7.20 and +3.08 fold in TG1-carrying pUC19 control plasmid and TG1 expressing native GFP, respectively, for defensive purposes against Cd-induced oxidative cell damage. Our findings strongly support the idea that complex formation between cadmium ions and His6GFP could prevent reactive oxygen species (ROS) caused by interaction between Cd2+ and electron transport chain. This coincided with the evidence that cells expressing His6GFP could maintain their growth pattern in a similar fashion as that of the control cells even in the presence of harmful cadmium. Interestingly, overexpression of either OmpA or His-OmpA in E. coli cells has also been proven to confer protection against cadmium toxicity as comparable to that observed in cells expressing His6GFP. Blockage of metal uptake as a consequence of anchored polyhistidine residues on surface membrane limited certain amount of cadmium ions in which some portion could pass through and exert their toxic effects to cells as observed by the increased expression of MnSOD of up to +9.91 and +3.31 fold in case of TG1 expressing only OmpA and His-OmpA, respectively. Plausible mechanisms of cellular responses and protein mapping in the presence of cadmium ions were discussed. Taken together, we propose that the intracellular complexation of cadmium ions by metal-binding regions provides more efficiency to cope with cadmium stress than the blockage of metal uptake at the surface membrane. Such findings provide insights into the molecular mechanism and cellular adaptation against cadmium toxicity in bacteria.
Keywords: Cadmium stress; Polyhistidine; Proteomics; Metal complexation; Outer membrane protein